A Comparison of Buprenorphine + Naloxone to Buprenorphine and Methadone in the Treatment of Opioid Dependence during Pregnancy: Maternal and Neonatal Outcomes - Ingunn O. Lund; Gabriele Fischer; Gabrielle K. Welle-Strand; Kevin E. O'grady; Kimber Debelak; William R. Morrone; Hendrέe E. Jones (SAGE Publishing, 2013)
Given that buprenorphine + naloxone is prescribed for opioid-dependent pregnant women, it is important to examine the extent to which it differs from buprenorphine alone, methadone, or methadone-assisted withdrawal on neonatal and maternal outcomes. Summary statistics on maternal and neonatal outcomes were collected from 7 previously published studies examining treatment for opioid-dependent pregnant women that represented a range of research methodologies. Outcomes from these studies were compared to the same outcomes for 10 women treated with the combined buprenorphine + naloxone product. There were no significant differences in maternal outcomes for buprenorphine + naloxone compared to buprenorphine, methadone, or methadone-assisted withdrawal. Preliminary findings suggest no significant adverse maternal or neonatal outcomes related to the use of buprenorphine + naloxone for the treatment of opioid dependence during pregnancy. However, further research should examine possible differences between buprenorphine + naloxone and buprenorphine alone or methadone in fetal physical development.